PENDIDIKAN KARAKTER DI SDN PEMURUS DALAM 7 BANJAR INDAH II KEC. BANJARMASIN SELATAN KOTA BANJARMASIN - Syamsir Ramadhan (ADDABANA: Jurnal Pendidikan Agama Islam, 2018)
The background of this research is based on the thought of educational problems characterized by the elementary level. Among the causes is that the education applied does not have a good concept of character education, so it has implications for the low level of education. Character education is chosen as an educational model because it is believed that this model will improve education and facilitate the achievement of character education goals. The Problem Formulation of this research is how character education and what factors influence character education in the effort of developing education and improving character education in accordance with the expectations and desires of education in Pemurus Dalam 7 SDN Banjar Indah II Kec. The South Banjarmasin City of Banjarmasin. The aim to be achieved in this study was to find out the character education in SD Pemurus Dalam 7 Banjar Indah II Kec. The South Banjarmasin City of Banjarmasin and the factors that influence it. Data collection techniques used are observation, interviews, and documentation. Data processing is done by editing techniques, data classification and data interpretation, while data analysis techniques use qualitative descriptive analysis, by describing each data obtained and to get a conclusion, researchers use inductive methods of character education in the research location. Based on the results of research that has been done, it is known that overall character education in SDN Pemurus Dalam 7 can run well and effectively enough in accordance with the values of character education developed by schools in Pemurus Dalam 7 Elementary School. The factors that support character education are factors teacher, student factors, time factors, and environmental factors greatly support the implementation of character education. Keywords: Education, Character Building, Students